Clinical complete response achieved in patients with breast cancer liver metastasis after personalized treatment: a case report and literature review - Wang, Yuxiang; Jing, Na; Wang, Yu; Li, Ning (Frontiers in Oncology, 2026)
Patient-derived organoids (PDOs) have been demonstrated not only to predict the response to neoadjuvant chemotherapy but also to tailor the treatment options for advanced breast cancer to improve prognosis. Here, we first reported a case of breast cancer liver metastasis that obtained clinical complete response (cCR) after treatment with eribulin and capecitabine, which showed sensitivity in the organoid drug sensitivity testing, and we conducted a systematic literature review. Our case report further provides a scientific basis for the PDOs as a powerful preclinical model to predict individual treatment sensitivity and improve the treatment outcomes of patients with advanced breast cancer, especially those with refractory or heavily treated breast cancer.